Propagation of intense short-pulse laser in homogeneous near-critical density plasmas. (May 2016) - Habara, H; Nakaguchi, S; Uematsu, Y; Baton, S D; Chen, S N; Fuchs, J; Iwawaki, T; MacDonald, M; Nazarov, W; Rousseaux, C; Tanaka, K A
Abstract: Ultra intense laser light propagation in a homogeneous overdense plasma was investigated using a plastic foam target filling a polyimide tube. Laser propagation into overdense plasma was measured via Doppler red shift of the reflected laser light from the moving plasma at 0.3-0.4 of speed of light. We also observed strongly collimated electron beam possibly caused by the magnetic field surrounding the plasma channel, and high energy X-rays emitted via synchrotron radiation by the oscillating electrons inside the channel. These features imply that UIL propagates inside the overdense plasma as predicted in PIC calculation, and are very important for direct irradiation scheme of fast ignition.